Exploring trait affectionate communication and post sex communication as mediators of the association between attachment and sexual satisfaction. (1st December 2019) - Bennett, Margaret; LoPresti, Brittny J.; Denes, Amanda
Abstract: Using both attachment theory (Bowlby, 1969) and affection exchange theory (AET; Floyd, 2002), the current study examines the relationships between adult attachment styles, trait affection, post sex affectionate communication behavior, and sexual satisfaction. Through a serial mediation model tested with Hayes' (2013) SPSS PROCESS macro, the findings yield that those with insecure attachment styles have lower levels of trait affection, which predicts less post sex affectionate communication behavior, which in turn predicts lower levels of sexual satisfaction. There is also a direct significant relationship between insecure attachment styles and lower levels of sexual satisfaction. Although attachment anxiety and attachment avoidance were tested in separate analyses, the results yielded the same pattern for both variables. Implications for both theories are discussed. Additionally, future research is recommended to assist practitioners in developing therapy interventions for insecurely attached individuals.